1972
DOI: 10.1002/j.1551-8833.1972.tb02753.x
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Controlling Bacterial Populations in Potable Waters: Community Water Supply

Abstract: The waters in some of the community water‐supply systems in the US often contain a myriad of microorganisms that carry past the disinfection barrier. Although the majority of those that survive and flourish are not pathogenic, the situation presents a potential danger. Here is an article on the sort of organisms that contribute to the trouble, with a description of factors relating to propagation of the species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
3

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 27 publications
2
78
0
3
Order By: Relevance
“…Biological interactions provide another potential mechanism to explain the injury of enteric bacteria within aquatic systems. It is generally appreciated that excessive populations of noncoliform heterotrophic bacteria can suppress the enumeration of coliforms in water (Geldreich et al, 1972), although the precise mechanism is unclear. The possibility of biological interactions causing injury was investigated in our laboratory by examining the influence of pseudomonad populations on the enumeration efficiency and injury of a coliform.…”
Section: Other Stressorsmentioning
confidence: 99%
“…Biological interactions provide another potential mechanism to explain the injury of enteric bacteria within aquatic systems. It is generally appreciated that excessive populations of noncoliform heterotrophic bacteria can suppress the enumeration of coliforms in water (Geldreich et al, 1972), although the precise mechanism is unclear. The possibility of biological interactions causing injury was investigated in our laboratory by examining the influence of pseudomonad populations on the enumeration efficiency and injury of a coliform.…”
Section: Other Stressorsmentioning
confidence: 99%
“…The determination of the total number of heterotrophic bacteria (HPC) has been known to be a better indicator of water quality than the coliform test because many opportunistic pathogens are not in the coliform group. 3 Furthermore, a high HPC interferes with the determination of the coliforms. 4 The present HPC method using R2A agar is the most sensitive test for enumerating the total number of bacteria in treated water.…”
Section: Introductionmentioning
confidence: 99%
“…The role of saprophytic bacteria in water as a better indicator of water quality than coliform index has been questioned (3,15,16). The bacteriological examination of the 40 sites revealed that during the course of study the saprophytic bacteria ranged A3 A5 A7 A9 A11 S1 S3 S5 S7 S9 S11 S13 R1 R3 R5 R7 R9 R11 A3 A5 A7 A9 A11 S1 S3 S5 S7 S9 S11 S13 R1 R3 R5 R7 R9 R11 R13 July 0 5 10 15 20 25 30 35 40 45 A1 A3 A5 A7 A9 A11 S1 S3 S5 S7 S9 S11 S13 R1 R3 R5 R7 R9 R11 R13 September 0 5 10 15 20 25 30 35 40 45 A1 A3 A5 A7 A9 A11 S1 S3 S5 S7 S9 S11 S13 R1 R3 R5 R7 R9 R11 R13 between 0.8 )/10 3 and 8.4 )/10 6 ; however, STSB ranged from 0.5 )/10 3 to 5.0 )/10 6 cfu/100 ml.…”
Section: Resultsmentioning
confidence: 99%